Degradação em processamento, cinética de cristalização e policondensação no estado sólido de poli(ácido láctico) - Gonçalves, Lívia Maria Garcia (2018)
In this work, the degradation of poly (lactic acid) (PLA) within conditions of high temperature, shear stress and humidity was studied. In addition to that, the crystallization kinetics of these degraded materials was assessed. The two topics were studied in order to be applied as controlled variables in the process of Solid State Polymerization (SSP) as an attempt to increase molecular weight of these materials. The degradation was promoted in a closed mixing chamber of a torque rheometer with discrete conditions of temperature and humidity. The degraded samples were characterized by techniques as Size Exclusion Chromatography (SEC), quantification of acidic percentages and Nuclear Magnetic resonance (NMR). The obtained data has enabled the comprehension of some of the degrading mechanisms involved in the processing, and its correlation to possible results of the posterior SSP process. Polymers with up to 50% reduction of molecular weight were obtained. The coefficients of the Avrami equation were determined for the purpose of control annealing treatments, which were mandatory before the SSP. Good correlation between the theoretical and practical values of crystallization were obtained, as well as the desired crystallographic phases, with the variation of temperature. Solid State Polymerization, however, has not lead to the desired results of increasing molecular weight, possibly due to small concentration of chain ends, even with the chain scissions induced by degradation